The Strategic Role of Leadership: Realizing a Value-Based Digital Transformation in Islamic Boarding Schools - Permata, Aldes Cyntia; Nugroho, Aris Dwi; Chaniago, Fransisko (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the strategic role of leadership in implementing digital transformation at Pondok Pesantren Ash-Shiddiiqi in the era of globalization, focusing on the integration of Islamic values, adaptive and exemplary leadership, human resource capacity development, external collaboration, and strategic communication. The research employed a qualitative case study approach, involving in-depth interviews, participatory observation, and document analysis to gain a comprehensive understanding of leadership practices and digitalization in the pesantren. The findings indicate that values-based leadership enables sustainable digitalization without compromising the identity of the pesantren, while adaptive and exemplary leadership enhances the collective capacity of teachers and staff through collaborative learning. Collaboration with alumni, government agencies, and other stakeholders strengthens resource support and institutional innovation, whereas transparent and Qur’anic principle-based communication effectively mitigates resistance to change. The integration of religious values, moral exemplarity, and technological adaptation creates a harmonization between digital innovation and spiritual orientation, reinforcing leadership legitimacy and ensuring the sustainability of the transformation. These findings contribute to the literature on transformational and adaptive leadership in Islamic education and provide practical guidance for other pesantren and Islamic educational institutions in managing digital transformation sustainably, aligned with institutional missions, and responsive to global challenges